Comparative effectiveness of devices for interventional patent foramen ovale closure: insights from a 23-year monocentric analysis - Kayvanpour, Elham; Matzeit, Elena; Kaya, Ziya; Pleger, Sven Torsten; Bahrmann, Anke; Reichardt, Christine; Ringleb, Peter A.; Frey, Norbert; Meder, Benjamin; Sedaghat-Hamedani, Farbod (Journal of Clinical Medicine, 2024)
Background/Objectives: Patent foramen ovale (PFO) is a congenital heart defect affecting up to 25% of the population, associated with an increased risk of cryptogenic stroke. Percutaneous PFO closure is a minimally invasive procedure aimed at reducing stroke risk by eliminating the right-to-left shunt. Methods: This monocentric, retrospective study analyzed 716 patients who underwent PFO closure between January 2000 and February 2023. Data collected included demographics, indications for closure, procedural details, and outcomes. Key endpoints were complications at the puncture site, pericardial effusion, recurrent stroke or transient ischemic attack (TIA), thrombi on the device, new-onset atrial fibrillation, and death. Results: The cohort had a mean age of 50.6 ± 12.6 years, with 60.8% female. Four devices were used: Occlutech PFO occluder (n = 106), Amplatzer PFO occluder (n = 227), Gore septal occluder (n = 296), and Cardia PFO-Star (n = 87). The initial procedural success rate was 98.9%, with no significant differences between devices. Complication rates were low across all devices. Residual shunt incidence decreased from 17.9% in 1 month to 3.4% in 12 months. Device-specific complications included late-onset pericardial effusion (p = 0.01), erosions (Cardia PFO-Star), and device thrombus formation (Gore septal occluder). Conclusions: PFO closure is a safe and effective method for preventing recurrent strokes, with high success rates and varying specific complication profiles, depending on the device. Further long-term studies are needed to evaluate newer devices and optimize patient outcomes.
Gesehen am 24.04.2025